Novel Aspects on Cysticercosis and Neurocysticercosis - Foyaca Sibat, Humberto (IntechOpen, 2013)
This book includes selected peer-reviewed chapters which cover novel aspects of cysticercosis and neurocysticercosis written by well known international researchers, representing the most relevant Working Group for Cysticercosis of Mexico, Peru, Ecuador, most of the Eastern and Southern Africa countries and Europe plus other contributions from Canada and United States of America. Unfortunately, our colleagues from Asia could not participate in this project for several reasons but we hereby acknowledge their contribution to the scientific level reached by the international scientific community. Apart from the classic issue that cannot be missing in any book about cysticercosis/ neurocysticercosis, we introduced a new hypotheses and novel aspects on historical background, clinical descriptions, investigations, and treatment modalities related to this zoonotic parasitic disease as a leading cause of epilepsy in developing countries. We are looking forward with confidence and pride in the vital role that this book will play for a new vision and mission.